Model Kepemimpinan Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru Pada SMKS Sayid Sabiq Indramayu - Didin Kurniadin; Nelly Maryani (LPPM Bunga Bangsa Cirebon, 2022)
This study discusses the principal's leadership model in improving teacher professionalism at Sayid Sabiq Indramayu Vocational School. This study is motivated by the principal's leadership model in improving the quality of learning and teacher competence optimally to achieve teacher professionalism. This study aims to determine the principal's leadership model in improving teacher professionalism at Sayid Sabiq Indramayu Vocational School. The method used in this research is descriptive qualitative method with data sources in the form of primary and secondary data. While data collection is done through observation, interviews, and documents. Based on the results of research and discussion, it was found that the principal's leadership model in increasing professionalism at the Sayid Sabiq Indramayu Vocational School was carried out with a collegial collective leadership model where this leadership characteristic has the concept that a leader is not only influenced by the traits that exist in a person, but can also be influenced by the accompanying group. The strategies carried out by the principal to improve the competence of professional teachers, including that the principal of SMKS Sayid Sabiq Indramayu has provided good services or actions, starting from the Principal conducting Teacher Working Groups (KKG), holding training (Diklat), Subject Teacher Consultations (MGMP) and involve teachers in improving teacher professionalism at the Sayid Sabiq Indramayu Vocational School. Abstrak Penelitian ini membahas model kepemimpinan kepala sekolah dalam meningkatkan profesionalisme guru pada SMKS Sayid Sabiq Indramayu. Kajian ini dilatar belakangi oleh model kepemimpinan kepala sekolah dalam meningkatkan kualitas pembelajaran dan kompetensi guru secara optimal untuk mencapai profesinalisme guru. Penelitian ini bertujuan untuk mengetahui model kepemimpinan kepala sekolah dalam meningkatkan profesionalisme guru pada SMKS Sayid Sabiq Indramayu. Metode yang digunakan dalam penelitian adalah metode kualitatif deskriptif dengan sumberdata berupa data primer dan sekunder. Sedangkan pengumpulan data dilakukan melalui observasi, wawancara, dan dokumen. Berdasarkan hasil penelitian dan pembahasan ditemukan bahwa model kepemimpinan kepala sekolah dalam meningkatkan profesionalisme pada SMKS Sayid Sabiq Indramayu dilakukan dengan model kepemimpinan kolektif kolegial dimana karakteristik kepemimpinan ini memiliki konsep bahwa seorang pemimpin tidak hanya dipengaruhi oleh sifat-sifat yang ada pada seseorang, tetapi dapat juga dipengaruhi oleh kelompok yang didampinginya. Adapun strategi yang dilakukan kepala sekolah untuk meningkatkan kompetensi guru yang professional, diantaranya bahwa kepala sekolah SMKS Sayid Sabiq Indramayu telah memberikan pelayanan atau tindakan yang baik dari mulai Kepala Sekolah melakukan Kelompok Kerja Guru (KKG), mengadakan pelatihan (Diklat), Musyawarah Guru Mata Pelajaran (MGMP) dan mengikut sertakan para guru dalam meningkatkan Profesionalisme guru di SMKS Sayid Sabiq Indramayu.